Stiff-Soft Hybrid Biomimetic Nano-Emulsion for Targeted Liver Delivery and Treatment of Early Nonalcoholic Fatty Liver Disease - Juan Li; Mingxing Yin; Maoxian Tian; Jianguo Fang; Hanlin Xu (MDPI AG, 2024)
Background: Nonalcoholic fatty liver disease (NAFLD) poses a risk for numerous metabolic diseases. To date, the U.S. Food and Drug Administration has not yet approved any medications for the treatment of NAFLD, for which developing therapeutic drugs is urgent. Dihydromyricetin (DMY), the most abundant flavonoid in vine tea, has been shown to be hepatoprotective. Its application was limited by low bioavailability in vivo; Methods: In order to improve the bioavailability of DMY and achieve liver-targeted delivery, we designed a DMY-loaded stiff-soft hybrid biomimetic nano drug delivery system (DMY-hNE). The in vivo absorption, distribution, pharmacokinetic profiles, and anti-NAFLD efficacy of DMY-hNE were studied; Results: DMY-hNE was composed of a stiff core and soft shell, which led to enhanced uptake by gastrointestinal epithelial cells and increased penetration of the mucus barrier, thus improving the in vivo absorption, plasma DMY concentration, and liver distribution versus free DMY. In an early NAFLD mouse model, DMY-hNE effectively ameliorated fatty lesions accompanied with reduced lipid levels and liver tissue inflammation; Conclusions: These findings suggested that DMY-hNE is a promising platform for liver drug delivery and treatment of hepatopathy.